Decision Support System for Acceptance Scholarship with Simple Additive Weighting Method - Kurniawan, Yogiek Indra (Universitas Muhammadiyah Surakarta, 2015)
A large number of scholarships have been extensively distributed in the educational institutions including college and university. It is, however, vulnerable to subjectivity. In general, students applying for the scholarship will be selected by the committee that may be subjective in the assessment process. In consequence, it can affect the result of scholarship recipients. Decision Support System (DSS) is a computer-based information system that supports the decision activities to be more. One method of the application of decision support systems is Simple Additive Weighting (SAW). This study was exploring the application of SAW in the case study of scholarship recipient selection process by weighting some predetermined criteria.